The Italian Diaspora in South Africa: Origins and Identity. (2nd October 2021) - Marchetti-Mercer, Maria; Virga, Anita
ABSTRACT: This  article reviews the history and legacy of Italian migration to South Africa since the seventeenth century, covering the colonial period under Dutch and British rule, the apartheid years (1948 to 1994), including the period after World War II, as well as developments in the Italian presence in the context of the post-1994 democratic dispensation. Unusual aspects of the roles of gender and religion are considered. Although several  studies have explored  Italian communities' experiences elsewhere in the world, little academic research has been conducted on the psycho-social experiences of the Italian community in South Africa. To address this lacuna, this article lays the foundations for a larger research project that was conducted on the experiences of second- and third-generation Italians in South Africa. It also identifies and stresses the need for further research into this part of the Italian diaspora in the context of the larger field of Italian studies.